Mitotic phosphorylation of SOX2 mediated by Aurora kinase A is critical for the stem-cell like cell maintenance in PA-1 cells. Issue 15 (2nd August 2016) - Qi, Dandan; Wang, Qianqian; Yu, Min; Lan, Rongfeng; Li, Shuiming; Lu, Fei
ABSTRACT: Transcription factor SOX2 is multiple phosphorylated. However, the kinase and the timing regulating SOX2 phosphorylation remains poorly understood. Here we reported mitotic phosphorylation of SOX2 by Aurora kinase A (AURKA). AURKA inhibitors (VX680, Aurora kinase Inhibitor I) but not PLK1 inhibitors (BI2536, CBB2001) eliminate the mitotic phosphorylation of SOX2. Consistently, siRNA inhibition of AURKA can eliminate mitotic SOX2 phosphorylation. Ser220 and Ser251 are two sites that identified for mitotic phosphorylation on SOX2. Moreover, SOX2 mutants (S220A and S251A) can promote SOX2 induced OCT4 re-expression in differentiated cells. These findings reveal a novel regulation mechanism of SOX2 phosphorylation mediated by AURKA in mitosis and its function in stem cell pluripotency maintenance in cancer cells.